Change in Acidity of L-Ascorbic Acid in the Mixed Solvent DMSO-Water Followed by Conductometric Determination of Dissociation Constants - Rimpapa, Zlatan; Pleho-Kapić, Amna; Galijašević, Semira; Šapčanin, Aida; Korać, Fehim (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2013)
Using conductometric method, the changes in the acidity of L-ascorbic acid in the mixed solvent dimethylsulfoxide (DMSO) - water were monitored. The mixed solvent used was two-component system consisting of nonpolar and polar solvents. Dissociation constants of L-ascorbic acid was determined in pure water and in the mixed solvent DMSO-water with different molar ratios of two solvents: xDMSO=0.500, 0.333, 0.250, 0.200, 0.166, corresponding respectively to DMSO-H2O, DMSO-2H2O, DMSO-3H2O, DMSO-4H2O, DMSO-5H2O. Concentrations of freshly prepared solution of ascorbic acid were in the range from 0.00002 to 0.05 moldm⁻³. Molar conductivity resistance values were measured for a given concentration of freshly prepared solutions of L-ascorbic acid and 24 hours old solutions. Using Ostwald's dilution law values for the molar conductivity at infinite dilution (l0) and dissociation constants (K), i.g. pK(-log K) were calculated. The results obtained for different concentrations of L-ascorbic acid in the mixed solvent DMSO-water indicate that during a time, pK values declined and acidity increased. Following pK values in the dependence on xDMSO for a freshly prepared solution of L-ascorbic acid, the curve with two inflection points was obtained corresponding to the system of mixed solvent DMSO and DMSO-2H2O and DMSO-3H2O. In 24 hours old solution of L-ascorbic acid, inflection points were not observed. The results indicate the possibility of different adducts in the mixed solvent or in old solutions as well as accumulation of degradation products over time.